Saturation recovery EPR and ELDOR at W-band for spin labels - Froncisz, Wojciech (2008)
A reference-arm W-band (94 GHz) microwave bridge with two sample-irradiation arms for saturation recovery (SR) EPR and ELDOR experiments is described. Frequencies in each arm are derived from 2 GHz synthesizers that have a common time-base and are translated to 94 GHz in steps of 33 and 59 GHz. Intended applications are to nitroxide radical spin labels and spin probes in the liquid phase. An enabling technology is the use of a W-band loop-gap resonator (LGR) (J.W. Sidabras et al., Rev. Sci. Instrum. 78 (2007) 034701). The high efficiency parameter (8.2 GW(−1/2) with sample) permits the saturating pump pulse level to be just 5 mW or less. Applications of SR EPR and ELDOR to the hydrophilic spin labels 3-carbamoyl-2,2,5,5-tetra-methyl-3-pyrroline-1-yloxyl (CTPO) and 2,2,6,6,-tetramethyl-4-piperidone-1-oxyl (TEMPONE) are described in detail. In the SR ELDOR experiment, nitrogen nuclear relaxation as well as Heisenberg exchange transfer saturation from pumped to observed hyperfine transitions. SR ELDOR was found to be an essential method for measurements of saturation transfer rates for small molecules such as TEMPONE. Free induction decay (FID) signals for small nitroxides at W-band are also reported. Results are compared with multifrequency measurements of T(1e) previously reported for these molecules in the range of 2 to 35 GHz (J.S. Hyde et al., J. Phys. Chem. B 108 (2004) 9524–9529). The values of T(1e) decrease at 94 GHz relative to values at 35 GHz.